Effects of Image-Sandplay Therapy on the Mental Health and Subjective Well-Being of Children with Autism - Juan Guo (Tehran University of Medical Sciences, 2021)
Background: Autism significantly affects mental health and lowers subjective well-being (SWB). The rehabilitation therapy of autism is attracting widespread attention. We aimed to explore the effects of image-sandplay therapy on the mental health and SWB of children with autism.